JNK suppression of chemotherapeutic agents-induced ROS confers chemoresistance on pancreatic cancer stem cells - Suzuki, Shuhei (Oncotarget, 2014)
Chemoresistance associated with cancer stem cells (CSCs), which is now being held responsible for the pervasive therapy resistance of pancreatic cancer, poses a major challenge to the successful management of this devastating malignancy. However, the molecular mechanism underlying the marked chemoresistance of pancreatic CSCs remains largely unknown. Here we show that JNK, which is upregulated in pancreatic CSCs and contributes to their maintenance, is critically involved in the resistance of pancreatic CSCs to 5-fluorouracil (5-FU) and gemcitabine (GEM). We found that JNK inhibition effectively sensitizes otherwise chemoresistant pancreatic CSCs to 5-FU and GEM. Significantly, JNK inhibition promoted 5-FU- and GEM-induced increase in intracellular reactive oxygen species (ROS), and scavenging intracellular ROS by use of N-acetylcysteine impaired JNK inhibition-mediated promotion of the cytotoxicity of 5-FU and GEM. Our findings thus suggest that JNK may contribute to the chemoresistance of pancreatic CSCs through prevention of chemotherapeutic agents-induced increase in intracellular ROS. Our findings also suggest that JNK inhibition combined with 5-FU- and/or GEM-based regimens may be a rational therapeutic approach to effectively eliminate pancreatic CSCs.